Pengaruh Metode TPR (Total Physical Response) Terhadap Kemampuan Berbahasa dan Kognitif Anak Speech Delay di PAUD - Nugraha Astutik, Maslamah; Hasibuan, Rachma; Khotimah, Nurul; Fitri, Ruqoyyah; Setyowati, Sri (Institut Agama Islam Negeri Madura, 2025)
The case of speech delay children in PAUD institutions in Ponorogo District has a high increase, there are 11 children who experience speech delays in PAUD. This study determined 4 speech delay children as research subjects. The TPR (Total Physical Response) method is applied to the learning process of speech delay children. This study aims to analyse the effect of Total Physical Response (TPR) method on language and cognitive development of speech delay children in PAUD. This research method is quantitative with the research design used for data analysis, namely the untreated control group design with pretest and postest which is a type of Control Group Time-Series Experiment, namely by conducting a pretest and posttest. The data collection technique is direct observation of the research subject during learning activities, and direct observation through documents of work, photos and videos of speech delay children. The results of observational data collected and analysed, as well as testing stated that there was an effect of the TPR method on the language and cognitive development of speech delay children in PAUD with evidence of the Wilcoxon test results which showed that language skills obtained an Asymp.Sig value. (2-tailed) 0.03 <0.05, while cognitive ability obtained an Asymp.Sig. (2-tailed) 0.011 < 0.05. For future research, it is recommended to conduct research on the effect of the TPR method on other aspects of development, namely religious and moral values, social emotional, physical motor and art.